Log of Apollo 11 - National Aeronautics and Space Administration, Washington, DC.; National Aeronautics and Space Administration, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
The major events of the first manned moon landing mission, Apollo 11, are presented in chronological order from launch time until arrival of the astronauts aboard the U.S.S. Hornet. The log is descriptive, non-technical, and includes numerous color photographs of the astronauts on the moon. (PR)
Availability: Superintendent of Documents, Government Printing Office, Washington, D.C. 20402 ($0.35, Stock No. 0-356-826).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Aerospace Education; Aerospace Technology; Instructional Materials; Lunar Research; Photographs; Resource Materials; Space Sciences; National Aeronautics and Space Administration -- Space Age